Digital Transformation and Regional Development: Regional Features in the Innovative Development of the Service Sector (On the Example of the Regions of Uzbekistan) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
In the context of accelerating digital transformation, the analysis of regional features in the innovative development of the service sector is becoming increasingly relevant. The article examines the relationship between digitalization, regional development, and service quality in the regions of Uzbekistan. Based on the experience of European countries (Estonia, Germany, Finland), the main factors contributing to the successful implementation of digital transformation at the local level have been identified. Cluster analysis, SWOT-assessment, and index modeling methods were used to assess the level of digital maturity in 12 regions of Uzbekistan (Tashkent, Samarkand, Fergana, Surkhandarya, and others). The results show that the introduction of digital platforms in the service sector increases the availability and quality of public services by 30-45%, especially in regions with developed information and communication technology infrastructure. At the same time, significant differences were found between central and peripheral regions. Recommendations have been developed for the harmonization of digital policy, strengthening interregional cooperation, and increasing the digital competence of the population.